Sparc a culturally integrated sport, arts and recreation community center in Navotas Fairview, Quezon City - Daway, Dianne Izzamae H. (College of Architecture, University of the Philippines Diliman, 2018)
SPARC aims to become a catalyst for development in the Novaliches Fairview area. It comprises of a proposal for the design of a new sports and recreation community center and a strip mall in context to the site. The overall proposal aims to create a more healthier and holistic environment for the people of Novaliches, Quezon City. This study and proposal incorporates agenda-based design as an architectural approach. SPARC Center aims to be a model for future sports and recreation facilities that focuses on the following agenda : Sports wellness, civic and community and an increase in economic factors. It utilizes site-specific approaches as responses that ill serve as urban interventions. SPARC is a primarily a new building typology in the Filipino community that is a combination of sports and recreation, arts and commercial spaces, that incorporates Filipino culture, experiential spaces and amenities that promote a more for the public. It features both public and private spaces that both residents and tourists to the area can enjoy. SPARC offers more than just the normal sports and play experience and aspires to invigorate its users to strive for a healthier lifestyle.